1996
DOI: 10.1210/en.137.5.1670
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian expression of insulin-like growth factor-I (IGF-I), IGF binding proteins, and growth hormone (GH) receptor in heifers actively immunized against GH-releasing factors

Abstract: Active immunization against GRF at 6 months of age delays puberty in beef heifers. The objectives of the present study were to determine whether active immunization against GRF at an earlier age would affect normal onset of puberty and follicular growth and to determine whether these changes were related to alterations in ovarian insulin-like growth factor I (IGF-I) or IGF binding protein (IG-FBP) messenger RNA (mRNA) levels. Heifers were immunized against human serum albumin (HSAi; n = 15) or against GRF conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…We did not see this relationship in follicle where there was no correlation between GHR and IGF-1. The absence of a significant correlation agrees with a study that showed little effect of GH on ovarian IGF-1 expression (Cohick et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…We did not see this relationship in follicle where there was no correlation between GHR and IGF-1. The absence of a significant correlation agrees with a study that showed little effect of GH on ovarian IGF-1 expression (Cohick et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…The relative importance of peripheral or locally produced levels of IGF-I to follicular development remains unclear, but data from the present study suggest that low concentrations of circulating IGF-I are related to low steroidogenic output of dominant ovarian follicles early PP. Furthermore, the results of a recent study strongly suggest that changes in systemic levels of IGF-I and IGFBPs affect their concentrations in follicular fluid and follicular development in heifers [42].…”
Section: Discussionmentioning
confidence: 99%
“…The IGFBP detected in serum included bands at approximately 44, 40, 34, 31, 29, 28, and 24 kDa. Although specific antibodies and deglycosylation techniques were not used to identify individual IGFBP bands, it can be deduced from previous studies that the 44-and 40-kDa bands were 2 different glycosylated forms of IGFBP-3, the 34 kDa band was IGFBP-2, IGFBP-5 migrated as a doublet at approximately 29 to 31 kDa, and the 24-and 28-kDa bands were nonglycosylated and glycosylated forms of IGFBP-4, respectively (Cohick et al, 1996;Funston et al, 1996;Roberts et al, 1997). The 44-and 40-kDa bands of IGFBP-3 and the 31-to 29-kDa bands of IGFBP-5 were not always distinguishable as individual bands on ligand blots.…”
Section: Weekmentioning
confidence: 99%